Henry Mason Morfit papers - Morfit, Henry Mason, -1868.
Correspondence and financial and business papers relating to Morfit's Washington, D.C., practice as a claims lawyer and as a minor political figure in the Jackson administrations. Correspondence primarily concerns business matters, especially the collection of claims. Other topics include slavery, French spoliation claims, land speculation in the South and West, finances, and patents. Correspondents include John Armstrong, Philip and Thomas Baltzell, George W. Campbell, Earl Douglas, John H. Eaton, William W. Eaton, Hugh Gelston, Joseph Giles, Duff Green, Jared Ingersoll, Thomas Ludlow, Alney McLean, Eustis Prescott, William H. Rhind, and Levi Woodbury.
Lawyer.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Armstrong, John, -- 1758-1843 -- Correspondence; Baltzell, Philip -- Correspondence; Baltzell, Thomas, -- -1866 -- Correspondence; Campbell, George Washington, -- 1769-1848 -- Correspondence; Douglas, Earl -- Correspondence; Eaton, John Henry, -- 1790-1856 -- Correspondence; Eaton, William W., -- newspaperman -- Correspondence; Gelston, Hugh -- Correspondence; Giles, Joseph, -- newspaperman -- Correspondence; Green, Duff, -- 1791-1875 -- Correspondence; Ingersoll, Jared, -- 1749-1822 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Ludlow, Thomas William, -- 1795-1878 -- Correspondence; McLean, Alney, -- 1779-1841 -- Correspondence; Prescott, Eustis -- Correspondence; Rhind, William H. -- Correspondence; Woodbury, Levi, -- 1789-1851 -- Correspondence; Claims; Finance; French spoliation claims; Land speculation -- Southern States; Land speculation -- West (U.S.); Patents; Practice of law -- Washington (D.C.); Slavery -- United States; United States -- Politics and government -- 1829-1837.; Lawyers